Analysis of failed discharge after ambulatory surgery: unanticipated admission. Issue 3 (4th May 2019) - Van Caelenberg, Els; De Regge, Melissa; Eeckloo, Kristof; Coppens, Marc
Abstract: Background: Advantages of ambulatory surgery are lost when patients need an unplanned admission. This retrospective cohort study investigated reasons for failed discharge and unanticipated admission of adult patients after day surgery. Methods: Ambulatory patients ( n = 145) requiring unanticipated admission were compared to patients ( n = 4980) not requiring admission and timely discharged from a total of 5156 ambulatory surgical procedures. Demographic data, organisational data, reason for admission, type of anesthesia, surgical discipline, length of procedure, ASA classification, surgical completion time and severity of illness score were collected from both groups. Reason for admission was classified according to four subtypes. Logistic regression analysis was used. Results: Incidence of unanticipated admission following day care surgery was 2.89%. The reasons for admission were mainly organisational issues (45.52%), time of completion surgery in the afternoon between 12 pm and 3 pm (OR 1.73; 95% CI 1.05–2.86) and surgery that ends after 3 pm (OR 6.52; 95% CI 4.11–10.34). Surgical factors associated with unanticipated admission (38.62%) were length of surgery of one to three hours (OR 2.05; 95% CI 1.27–3.29), length of surgery more than three hours (OR 8.31; 95% CI 3.56–19.40). Additionally, anaesthetic (10.34%) and medical (5.52%) reasons were found, e.g. ASA class II (OR 1.61; 95% CI 1.06–2.44), ASA class III (OR 2.19; 95% CI 1.10–4.34); moderate severity of illness score (OR 1.72; 95% CI 1.03–2.88) and major of severity of illness score (OR 7.85; 95% CI 2.31–26.62). Conclusions: Unanticipated admissions following day surgery occur mainly due to social/organisational and surgical reasons. However, medical and anaesthetic reasons also explain 15.86% of the unanticipated admissions.